Short-chain ceramides decrease skin barrier properties - Novotný, J; Janůsová, B; Novotný, M; Hrabálek, A; Vávrová, K (Skin pharmacology and physiology, 2009)
Stratum corneum ceramides are major determinants of skin barrier function. Although their physiological and pathological role has been widely investigated, to date no structure-activity relationships have been established. In this study, a series of short-chain ceramide analogues with polar head structure identical to ceramide NS, a sphingosine length of 12 carbons and an acyl chain length of 2-12 carbons was synthesized. Their effect on skin permeability was evaluated using porcine skin and two model drugs, theophylline and indomethacin, and compared to that of a physiological ceramide NS. The results showed that the ceramide chain length was crucial for their barrier properties. Ceramides with a 4- to 8-carbon acyl chain were able to increase skin permeability for both drugs up to 10.8 times with maximum effect at a 6-carbon acyl chain. No increase in permeability was found for ceramide analogues with 2- and 12-carbon acyl chains and ceramide NS. The same relationships were obtained for skin concentrations of the model drugs. The relationship between ceramide acyl chain length and its ability to perturb skin barrier showed striking similarity to the behavior of short-chain ceramides in sphingomyelin/phospholipid membranes and confirmed that short-chain ceramides do not act as natural ceramides and their use as experimental tools should be cautious.
Keywords: prasata; Swine; permeabilita; Structure-Activity Relationship; theofylin; molekulární struktura; Molecular Structure; Indomethacin; Ceramides; kůže; Theophylline; vztahy mezi strukturou a aktivitou; Permeability; Animals; Skin; ceramidy; zvířata; kožní absorpce; Skin Absorption; indomethacin